Beatitude e sabedoria em Agostinho : estudo sobre as fontes pagãs no De beata vita a partir do uso do termo philosophia - Beraldi, Adriano Cesar Rodrigues (2010)
The aim of this paper is to provide an analysis concerning the influxes of pagan thought about Aurelius Augustine (354-430), within the limits of his work De beata vita. This is one of the earliest writings of the initial cycle (from November of 386 to march of 387), the dialogues of the called “young Augustine”. For this, we resorted to the employ that the author makes of the term philosophia throughout the book as a conductor thread of our research. The images of philosophia developed from that use allow to expose the influences of pagan thought prior to our philosopher, as much as to feature his original conception on the central issue of the dialogue: the happiness. In this effort, we used others of his works of this initial period, once belong to the same speculative range. With this, we also tried to demonstrate how in this “first Augustine”, lies a possibility for the notion of happiness not only in an eschatological way, but even in this life.